An investigation of the pre-competition mental state characteristics of elite archers - Chi, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: A longitudinal series of studies was performed to explore the pre-competition mental state of elite archers. The aim of the study is to provide a strong experimental foundation for pre-competition psychological inventions. Methods Subjects were selected from the Chinese national archery team (the number of subjects varied between trials from 8 to 28). The inventories used were the Players` Training Monitoring Scale (Yanning, 2003), Flowing State Scale (Jackson & Marsh, 1995; Mingqiu Fu, et al, 2005), and the Athlete Burnout Questionnaire (Raedeke & Smith, 2001). The surveys were taken five times, during the winter training session and before qualifying games, during the Asian games, the archery championship, and the good luck Beijing games. Data was analyzed using SPSS 11.5. Results 1. The survey of training state showed that significant differences existed for five dimensions (wellbeing, tiredness, stress, self efficacy, self regulation and burnout) between the time points. The results on these were lower before the championship than at other time points. 2. No significant differences were found on the archers` burnout. 3. The survey of flow state revealed that significant differences existed on2 dimensions: clear goal and positive experience (P<.01). The results for 2 dimensions before the championship or the Good Luck Beijing Games were less than the scores at other time points. 4. Analysis of the data from the individual players showed that the mental characteristics of the archers were different. Some were stable on pre-competition mental state, whilst others were not. Discussion / Conclusions This study showed that the mental state of elite archery team players changed before competition. These findings might be related to factors such as the quality and intensity of training, performance in recent competitions and physical condition. The pre-competition mental states of individual archers were different. Monitoring of the mental states of elite archers should be connected with the monitoring of physiology, biochemistry and feedback from coaches, to ensure the validity of monitoring and intervention.